Explorations in computing : an introduction to computer science - Conery, John S. (Boca Raton, FL : CRC Press, 2011)
'Based on a course taught by the author, this textbook provides an introduction to computer science for non-majors or pre-majors in beginning courses. The book uses an active learning and problem-solving approach to present key topics in computer science, along with real-world examples and practical algorithms. The author explains how to read, rather than write, programs and how to solve problems. To provide a good understanding of computing without covering everything in the field, short focused chapters include tutorial projects and interactive labs that use Ruby, a simple open-source language.'--
'The title of this book, Explorations in Computing, conveys the idea of how we will use a similar active learning approach to study computation. Each chapter is organized around a single project that introduces an important concept or application in computer science. To complete the project, students type commands in Ruby, an interactive programming language,following a detailed script set out in the text. The aim is for the students to immerse themselves in the interactive environment, and experience first-hand what goes on inside a computer as it solves some interesting problems. Many parts of the projects are open-ended, and students are encouraged to continue exploring on their own, after using the exercises in the book as a starting point'--
Includes bibliographical references (p. 15) and index.
Keywords: Computer science